Thermoelectric power (TEP) and structural properties of ternary semiconducting V2O5– NiO–TeO2 glasses 1 - Tawatia, Daefalla; A. Husseina, Nagi; Ayada, Arwa; M. Mohammeda, Hana; A. Saltania, Hend; A. K. Arofb, A. K. Arofb (Libyan Journal of Science &Technology, 2022)
Thermoelectric power (TEP) and structural properties of ternary semiconducting V2O5– NiO–TeO2 glasses 1